Experiences of long-term life-limiting conditions among patients and carers: what can we learn from a meta-review of systematic reviews of qualitative studies of chronic heart failure, chronic obstructive pulmonary disease and chronic kidney disease?. Issue 10 (5th October 2016) - May, Carl R; Cummings, Amanda; Myall, Michelle; Harvey, Jonathan; Pope, Catherine; Griffiths, Peter; Roderick, Paul; Arber, Mick; Boehmer, Kasey; Mair, Frances S; Richardson, Alison
Abstract : Objectives: To summarise and synthesise published qualitative studies to characterise factors that shape patient and caregiver experiences of chronic heart failure (CHF), chronic obstructive pulmonary disease (COPD) and chronic kidney disease (CKD). Design: Meta-review of qualitative systematic reviews and metasyntheses. Papers analysed using content analysis. Data sources: CINAHL, EMBASE, MEDLINE, PsychINFO, Scopus and Web of Science were searched from January 2000 to April 2015. Eligibility criteria for selecting studies: Systematic reviews and qualitative metasyntheses where the participants were patients, caregivers and which described experiences of care for CHF, COPD and CKD in primary and secondary care who were aged ≥18 years. Results: Searches identified 5420 articles, 53 of which met inclusion criteria. Reviews showed that patients' and caregivers' help seeking and decision-making were shaped by their degree of structural advantage (socioeconomic status, spatial location, health service quality); their degree of interactional advantage (cognitive advantage, affective state and interaction quality) and their degree of structural resilience (adaptation to adversity, competence in managing care and caregiver response to demands). Conclusions: To the best of our knowledge, this is the first synthesis of qualitative systematic reviews in the field. An important outcome of this overview is an emphasis on what patients and caregivers value and on attributes of healthcare systems, relationships and practices that affect the distressing effects and consequences of pathophysiological deterioration in CHF, COPD and CKD. Interventions that seek to empower individual patients may have limited effectiveness for those who are most affected by the combined weight of structural, relational and practical disadvantage identified in this overview. We identify potential targets for interventions that could address these disadvantages. Systematic review registration number: PROSPERO CRD42014014547.